Distribution and physicochemical properties of particulate matter in swine confinement barns. (July 2019) - Shen, Dan; Wu, Sheng; Li, Zhaojian; Tang, Qian; Dai, Pengyuan; Li, Yansen; Li, Chunmei
Abstract: Air pollutants accumulated in confined livestock barns could impact the health of animals and staff. Particulate matter (PM) and ammonia (NH3 ) concentrations are typically high in enclosed livestock houses with weak ventilation. The objective of this study was to investigate the distribution of PM in different size fractions and the levels of NH3 in a high-rise nursery (HN) barn and a high-rise fattening (HF) barn on a swine farm and to analyse the physicochemical properties of fine PM (PM2.5, PM with aerodynamic diameter ≤ 2.5 μm). The concentrations of total suspended particles (TSP, PM with aerodynamic diameter ≤ 100 μm), inhalable PM (PM10, PM with aerodynamic diameter ≤ 10 μm), PM2.5 and NH3 were monitored continuously for 6 d in each barn. The results showed that the concentrations of PM and NH3 varied with position, they were significantly higher inside the barns than outside ( P  < 0.01) and significantly higher in the forepart than at the rear of the two barns ( P  < 0.05). In the HF barn, the values of the two parameters were 0.777 ± 0.2 mg m −3 and 26.7 ± 7 mg m −3, respectively, significantly higher than the values observed in the HN barn at all monitored sites ( P  < 0.05). The PM concentrations increased markedly during feeding time in the two barns. Chemical characteristics analysis revealed that the main sources of PM2.5 in the two barns may have consisted of blowing dust, feed, mineral particles and smoke. In conclusion, the air quality at the forepart was worse than that at the rear of the barns. Activities such as feeding could increase the PM concentrations. The components of PM2.5 in the two barns were probably blowing dust, feed, mineral particles and smoke from outside. Graphical abstract: Image 1 Highlights: It is important to control air pollution inside swine barns. The spatial variation in the PM and NH3 concentrations in swine barns was analysed. The PM and NH3 concentrations indicated contamination of the swine barns. The main sources of PM2.5 in swine barns are probably feed and manure.